The role of IRAK3 in regulating immune-mediated inflammatory arthritis - Borghese, F (2018)
A repeated or prolonged stimulation with LPS induces in macrophage-lineage cells a refractory state known as endotoxin tolerance (ET). ET curtails inflammation and prevents tissue damage caused by sustained immune activation in sepsis. TNFα is required for ET induction and it is hypothesized that TNFα exerts its immuno-modulatory action via ET-associated molecules. In models of TNFα-driven disease, ET-associated molecules were investigated to determine their role in the progression from acute, self-limiting inflammation to chronic inflammatory disease. An in vitro model of ET was developed to evaluate the gene expression profile of ET macrophages. The ET-associated genes IRAK3, TNFAIP3 and PTPN6 were further investigated in collagen-induced arthritis (CIA). Although arthritic paws had increased macrophage-lineage cell infiltration and high expression of TLRs and TNFα, the expression of ET-associated genes was not uniformly increased. Tnfaip3 and Ptpn6 were up-regulated in arthritic paws but Irak3, a key molecule in ET which inhibits the MyD88 pathway, was expressed at a lower level than the naïve control throughout the inflammatory process. CIA was performed in IRAK3-/- mice and WT controls. In IRAK3-/- mice the disease was significantly accelerated, inflammatory gene expression was higher in paws, plasma IL1β concentration was higher and there was a decrease in the prevalence of regulatory T cells in spleen and lymph-nodes. We hypothesize that an alteration in IRAK3 gene expression or activity potentiates the development and chronicity of inflammatory disease.